2021
DOI: 10.1186/s13100-021-00235-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic properties of variably methylated retrotransposons in mouse

Abstract: Background Transposable elements (TEs) are enriched in cytosine methylation, preventing their mobility within the genome. We previously identified a genome-wide repertoire of candidate intracisternal A particle (IAP) TEs in mice that exhibit inter-individual variability in this methylation (VM-IAPs) with implications for genome function. Results Here we validate these metastable epialleles and discover a novel class that exhibit tissue specificity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 85 publications
1
11
0
Order By: Relevance
“…Indeed, IAP transcripts are rarely detected in somatic tissues outside of tumours and early embryogenesis, but thymic and activated splenic cells are notable exceptions (Kuff and Lueders, 1988). In addition, young ERVs have recently been implicated in shaping the evolution of transcriptional networks underlying innate immunity (Chuong et al, 2016;Tie et al, 2018;Ye et al, 2020), and our group recently identified individual IAP elements that exhibit inter-individual methylation variability exclusively in B cells (Elmer et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Indeed, IAP transcripts are rarely detected in somatic tissues outside of tumours and early embryogenesis, but thymic and activated splenic cells are notable exceptions (Kuff and Lueders, 1988). In addition, young ERVs have recently been implicated in shaping the evolution of transcriptional networks underlying innate immunity (Chuong et al, 2016;Tie et al, 2018;Ye et al, 2020), and our group recently identified individual IAP elements that exhibit inter-individual methylation variability exclusively in B cells (Elmer et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Following our genome-wide screen for VM-IAPs in the B6 genome, DNA methylation at the distal CpGs of the 5′ LTR of each candidate was validated using genomic DNA (gDNA) extracted from adult inbred B6 mice (Elmer et al, 2021;Kazachenka et al, 2018). While VM-IAP DNA methylation levels display continuous probability distributions in the B6 population, the IAP-Pgm2 5′ LTR exhibited three distinct states: high (> 85%), low (< 20%), and intermediate (60-70%) methylation (Figure 1A and B).…”
Section: Iap-pgm2 Methylation Is Tri-modally Distributed In Inbred B6 Micementioning
confidence: 99%
See 1 more Smart Citation
“…In B and T cells of C57BL/6 J, DNA methylation levels in TEs of retroviral origin correlate inversely with CTCF binding. This indicates that there is a close relationship between DNA methylation and the regulation of chromatin status and loop formation ( 43 ) ( Figure 2 ).…”
Section: Regulation Of Erv Expression At Transcriptional and Post-tra...mentioning
confidence: 92%
“…In mice, variable methylation states have been associated with the Intracisternal A Particle (IAP) class of endogenous retrovirus 58,59 , with growing evidence that methylation variability may in part be driven by incomplete silencing of IAPs in early development [60][61][62] . In humans, SIV-CpGs are enriched for proximal endogenous retrovirus elements (ERVs) 63 , including the subclasses ERV1 and ERVK 26 .…”
Section: Hvcpgs Are Enriched For Parent-of-origin Methylation and Proximal Tesmentioning
confidence: 99%